2003
DOI: 10.1149/1.1573200
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Mechanical Properties of Surfactant Templated Nanoporous Silica Thin Films: Effect of Methylsilylation

Abstract: Microstructural and mechanical properties of organic surfactant templated nanoporous thin silica films have been studied by X-ray diffraction, Fourier transform infrared spectroscopy, and nanoindentation. Compared with many other porous low-k dielectrics, the self-assembled molecularly templated nanoporous silica films demonstrate better mechanical properties. This is ascribed to the presence of a well-ordered pore channel structure in the nanoporous silica thin films. Hardness and elastic modulus are strongly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 24 publications
0
24
0
Order By: Relevance
“…The cause of this deterioration has often been attributed to the absorption of airborne contaminants and overall water vapour in the film pores, leading to an increase in the refractive index [8][9][10][11]. Additionally, it has been reported that, this adsorption degrades not only the optical properties but also the electrical properties of porous silica films [12,13].…”
Section: Durability Of Antireflective Filmsmentioning
confidence: 99%
“…The cause of this deterioration has often been attributed to the absorption of airborne contaminants and overall water vapour in the film pores, leading to an increase in the refractive index [8][9][10][11]. Additionally, it has been reported that, this adsorption degrades not only the optical properties but also the electrical properties of porous silica films [12,13].…”
Section: Durability Of Antireflective Filmsmentioning
confidence: 99%
“…The drawbacks of these porous films include the presence of hydrophilic silanol groups on the internal wall surfaces and the lack of mechanical strength (e.g., elastic modulus, hardness). Although the silanol groups can be transformed to the hydrophobic moieties by treatment with hexamethyldisilazane (HMDS) [1][2][3][4], the mechanical strength of the resulting films is insufficient as ULSI interconnects.…”
Section: Introductionmentioning
confidence: 99%
“…Periodic surfactant-templated film systems with large degrees of nanoscale order have shown moduli in the range of 10±13 GPa. [6,27] Although some of these numbers have been derived from nanoindentation experiments that may overestimate moduli, [28±30] it is clear that these numbers are lower than the thin films in the parallel orientation in this study. This comparison shows that the alignment effects observed in this work must be central in determining the modulus of the films.…”
Section: Full Papermentioning
confidence: 78%
“…Furthermore, surfactanttemplated porous silica films with large degrees of nanoscale order have shown moduli in the range of 10±13 GPa. [6,27] Although many of the moduli discussed above should be treated with caution because nanoindentation experiments can overestimate elastic moduli owing to the viscoelasticity of the film, substrate stiffening, and film±tip interactions, [28±30] the average moduli for ordered systems are clearly larger than those of the disordered systems addressed above. This trend is clear whether the material is present in bulk or thin-film forms, indicating that nanoscale architecture is an important variable that contributes to the mechanical properties in these systems.…”
mentioning
confidence: 99%